Architecture of RAM-Accumulator based Multichannel Digital PWM - Norma Hermawan (JAREE (Journal on Advanced Research in Electrical Engineering), 2017)
Traditional counter based digital Pulse Width Modulator (PWM) has been a straightforward architecture. However, realization of multichannel PWM with such design requires considerable logic gates. A novel architecture of multichannel PWM based on the usage of RAM block and frequency word accumulator is proposed. This architecture is capable of producing numerous channels while maintaining its performance. The design was tested in Microsemi SmartFusion A2F200 Customizable System on Chip, giving the result of 7.73% FPGA usage to produce 48 channels of 380Hz 16 bits PWM. The output performance for test application is acceptable. Keywords: PWM; RAM; accumulator; multichannel; digital